Decline in the share of the agricultural product: measurements and explanations - ERCOLANI, P. (PSL Quarterly Review, 2013)
The reduction of agriculture’s share of product constitutes the most important change in the structure of supply associated with income growth. This is so constant that it can be considered one of the “laws” of economics, however, in order to understand such a complex phenomenon in terms of economic development, the search for uniformity should represent only the beginning, not the conclusion of the analysis. This work focuses on the pattern of agriculture’s share, both among countries and over time, and considers the factors which determine the relative decline of the agricultural product. The author singles out the factors other than income that have contributed to the determination of systemic differences among countries in agriculture’s share in product. Then, a quantitive assessment of the factors which have caused the decline is presented. JEL: N50, O13, Q10